2021
DOI: 10.1590/1806-9665-rbent-2020-0083
|View full text |Cite
|
Sign up to set email alerts
|

First report of Spodoptera frugiperda (Lepidoptera: Noctuidae) on Onion (Allium cepa L.) in South Kivu, Eastern DR Congo

Abstract: The fall armyworm, Spodoptera frugiperda (J. E. Smith, 1797), has become one of the most devastating pests in the world with diverse host range. To develop effective integrated management strategies against S. frugiperda, it is crucial to know its alternative host plants. In this study, we provide the first information on the occurrence of S. frugiperda in onion crops in Africa. Monitoring was carried out during the 2019 and 2020 growing seasons in onion monoculture and in intercropping with groundnut to detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Similar to the studies by Kumela et al (2019); Houngbo et al (2020); Caniço et al (2021), this study indicated that farmers recognize FAW well and the majority of them already had damage in their maize crops. Furthermore, four plant species were recorded as alternative hosts of FAW including onion which was previously reported by Cokola et al (2021b). The other crops reported, namely cabbage, sorghum and Napier grass, constitute new information that could help researchers and governments in the development of an integrated approach against FAW on the African continent.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Similar to the studies by Kumela et al (2019); Houngbo et al (2020); Caniço et al (2021), this study indicated that farmers recognize FAW well and the majority of them already had damage in their maize crops. Furthermore, four plant species were recorded as alternative hosts of FAW including onion which was previously reported by Cokola et al (2021b). The other crops reported, namely cabbage, sorghum and Napier grass, constitute new information that could help researchers and governments in the development of an integrated approach against FAW on the African continent.…”
Section: Discussionsupporting
confidence: 58%
“…Nevertheless, in its native region, it can establish more than 350 plant species, of which 80 are commonly cultivated plants such as maize, sorghum, rice, or cotton (Montezano et al, 2018). Because of this polyphagous nature, FAW can establish and adapt well in a newly invaded area by attacking other crops, usually vegetable crops (Cokola et al, 2021b). Its rapid spread across the African continent is causing significant yield losses to maize crops for tens of millions of smallholder farmers who depend on this crop for their food security (Day et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Insects, nematodes, and weeds are also responsible for severe yield losses. Important insect pests affecting major crops in the region include fall armyworm ( Spodoptera frugiperda ), tomato leafminer ( Tuta absoluta ), coffee bugs ( Antestiopsis orbitalis ghesquierei ), whitefly ( Bemisia tabaci ), banana aphid ( Pentalonia nigronervosa ), and coton aphid ( Aphis gossypii ) ( Nyabyenda, 2005 ; Dushimirimana et al., 2016 ; MINAGRI-Burundi, 2018 ; Niyibizi et al., 2019 ; Belga, 2020 ; Mukwa et al., 2020 ; Cokola et al., 2021 ; Niassy et al., 2021 ). The control of these insects relies heavily on the use of synthetic products such as acephate against S. frugiperda and T. absoluta , chlorpyrifos-ethyl against A. orbitalis ghesquierei and imidacloprid against aphids.…”
Section: Diversity Of Phytopathogens and Their Controlmentioning
confidence: 99%
“…It was also reported that S. frugiperda attacked shallots in South Kivu, DR Congo Province [6]. The losses that occur in corn plants due to pest attacks in African and European countries are between 8.3 to 20.6 million tons per year with an economic loss value of between US $ 2.5-6.2 billion per year [7].…”
Section: Introductionmentioning
confidence: 98%